Principles of Economics - N. Gregory Mankiw (Thomson/South-Western, 2007)
Principles of Economics continues to be the most popular and widely used text in the Economics classroom. The 4th edition features a strong revision of content in all 36 chapters while maintaining the clear and accessible writing style that is the hallmark of the highly respected author. The 4th edition also features an expanded instructor's resource package designed to assist instructors in course planning and classroom presentation and full integration of content with Aplia, the leading online Economics education program